2002
DOI: 10.1203/00006450-200203000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Postischemic Hypothermia Improves Long-Term Behavioral Outcome after Cerebral Hypoxia-Ischemia in Neonatal Rats

Abstract: Hypothermia may be an ideal neuroprotective intervention in hypoxic-ischemic encephalopathy after perinatal asphyxia. The present study describes the long-term effects of prolonged resuscitative whole-body hypothermia initiated 2 h after hypoxicischemic injury on brain morphology and neuropsychological behavior in 7-d-old rats. After right common carotid artery ligation and exposure to hypoxia of 8% O 2 for 105 min, 10 animals were kept normothermic at 37°C and 10 animals were cooled to 30°C rectal temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
70
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 48 publications
15
70
1
3
Order By: Relevance
“…Some of these reports have described a reduction by 42%-65% of the injured area when using hypothermia as neuroprotective strategy (30,31), a proportion very similar to that obtained with WIN. In addition, WIN reduced the shrinkage of the ipsilateral hemisphere observed after HI.…”
mentioning
confidence: 61%
“…Some of these reports have described a reduction by 42%-65% of the injured area when using hypothermia as neuroprotective strategy (30,31), a proportion very similar to that obtained with WIN. In addition, WIN reduced the shrinkage of the ipsilateral hemisphere observed after HI.…”
mentioning
confidence: 61%
“…By using a flexible temperature probe, rectal temperature was measured at 1 and 4 h, and thereafter every 4 h until the end of each intervention period. Through the period of temperature intervention, pups were fed five times per day with 0.4 mL of commercially available ready-to-feed formula by using 22G-animal feeding needle with round (15). After temperature intervention, the pups were returned to their dams until the end of imaging studies and functional studies at 5 wk postinsult.…”
Section: Animal Model Of Hiementioning
confidence: 99%
“…The 7-d-old rat with unilateral carotid artery ligation and subsequent exposure to 8% hypoxia is the most commonly used model to evaluate the efficacy of therapeutic interventions in the developing brain (12), and several studies have used this Rice-Vannucci model (RVM) to test the effects of HT (10,11,(13)(14)(15)(16)(17)(18)(19). However, an experimental design composed of a shorter duration of hypoxia, representing "mild" ischemic lesions, is not appropriate for evaluating the neuroprotective effect of HT against severe HIE.…”
mentioning
confidence: 99%
“…After hypoxic exposure, pups that have formed an experimental group were returned to their dams. Because it has been shown that carotid artery ligation without hypoxia (sham) produced neither brain damage 9 nor functional impairments in rodents, 10,11 control animals consisted of age-and strain-matched naïve (no HI) mice.…”
Section: Murine Model Of Hiementioning
confidence: 99%